P-470 Impact of patient characteristics at ovarian tissue cryopreservation on follicle activation and survival. (30th June 2022) - Devos, M; Vidal, P. Diaz; Anckaert, E; Dolmans, M.M; Demeestere, I
Abstract: Study question: Does first-line chemotherapy prior to ovarian tissue cryopreservation and diseases impact on the signaling pathways governing follicle activation and survival in pre-pubertal and adult patients? Summary answer: Chemotherapy increases follicle apoptosis rate without affecting early follicular activation. Moreover, damages varied according to the time of last exposure and the diseases. What is known already: Chemotherapeutic agents can impair the ovarian stockpile inducing a decrease of the reproductive potential of female cancer survivors. Among fertility preservation methods, cortical tissue cryopreservation is offered in patients who already started their treatment or cannot postpone it, and it is currently the only available procedure for pre-pubertal patients. Few studies did not report negative impact of prior first-line chemotherapy on ovarian tissue cryopreservation outcomes, the consequences of the treatment on the follicle activation in human remain to be further investigated. Identifying the signaling modifications induced by chemotherapy exposure is essential to address this question. Study design, size, duration: Fragments of cryopreserved ovarian tissue from young adult (12-29 years old, n = 8) and pre-pubertal (3-10 years old, n = 7) cancer patients donated for research were thawed and cultured for 24h. Analyses of the follicle and stroma survival, as well as the PI3K/AKT/mTOR and Hippo signaling pathways were conducted at thawing and after culture. The different patients were grouped according to their pubertal stage and those who received chemotherapy before ovarian banking were compared to non-exposed patients. Participants/materials, setting, methods: To assess the distribution and morphology of the follicles, the structure of the stroma, and the apoptosis, histological investigations were performed through follicular counting, Sirius Red staining, immunostaining, and TUNEL staining. The PI3K/AKT/mTOR and Hippo signaling pathways were investigated to explore the follicular activation among the different groups by gene expression and protein analyses on isolated follicles and cortex, respectively. Main results and the role of chance: The deleterious impact of chemotherapy exposure prior to tissue banking was observed specifically on quiescent follicles by TUNEL staining at thawing and after culture in both adult and pre-pubertal patients. After 24h of culture, tissues previously exposed to chemotherapy displayed a higher rate of follicles containing DNA damages than the non-exposed fragments in adults (40.9% versus 19.1%), and pre-pubertal (48.3% versus 17.6%) patients. The atresia rates and DNA damages appeared to be lower into the tissue of patients that received their last cure 4-5 months before the cryopreservation among the treated adult and pre-pubertal groups. DNA reparation mechanisms were assessed through gH2Ax staining and revealed a correlation with the diseases as a higher phosphorylation rate of H2Ax protein was observed in tissues from acute leukemia patients compare to the others at thawing (p = 0.009) and after 24h (p < 0.001). Although protein analyses on Kit Ligand, key regulator of the follicle activation, showed an increase of expression into the groups treated by chemotherapy, genes and protein involved in the PI3K/AKT/mTOR and Hippo pathways showed similar expression levels in the chemo-treated groups compared to the non-exposed groups, irrespective of the age. Limitations, reasons for caution: The study of follicle survival was limited to histological analyses, while follicular activation evaluations were limited to the evaluation of two main signaling, PI3K/AKT/mTOR and Hippo. Moreover, considering the heterogeneity of the human model, and the limited number of patients included, the results should be interpreted with caution. Wider implications of the findings: Our results highlight the deleterious impact of previous chemotherapeutic treatment on follicle survival without affecting follicular activation. Besides sustaining the "burn out effect" theory, our results suggested that the time of last exposure and the pathology of the patient could impact the outcomes of the cryopreserved ovarian tissue. Trial registration number: not applicable